Hooked Online: Unmasking the Risks of Internet Addiction Among Gen Z Youths - Tek Yew Lew; Azura Abdullah Effendi; Garima Mathur; Sashmitha Nair Suthesh; Selva Ganesh A/L Muthupalaniappan; Shahira Binti Akhter Ali; Xue Wen Shao; Daisy Mui Hung Kee (Journal of The Community Development in Asia, 2026)
With the widespread availability of digital devices and internet access, Gen Z youths are increasingly susceptible to internet addiction. This study investigates the complex and interconnected risks associated with excessive internet use, including mental health challenges, pornography addiction, cyberbullying, and other emerging concerns. Using a quantitative approach through a survey of 150 Gen Z, this paper uncovers significant links between internet addiction and negative outcomes in youth development and daily functioning. The results highlight the pressing need for interventions, policy responses, and awareness initiatives to mitigate the impact of internet addiction and safeguard youth well-being